Pengaturan Hak-hak Masyarakat Adat atas Sumber Daya Alam Berdasarkan Internasional Covenant On Economic, Social and Cultural Rights (ICESCR) - Sahlan, Sahlan; Anwar, Arman; Wattimena, Josina Augustina Yvonne (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: According to national law, the protection of the rights of indigenous peoples has been regulated in Law Number 11 of 2005 concerning ratification of the ICESCR, but in practice violations of the rights of indigenous peoples still occur.Purposes of the Research: This writing aims to examine and find out the arrangements for the rights of indigenous peoples over natural resources based on the ICESCR and the rights of indigenous peoples on natural resources that have been implemented in accordance with the ICESCR.Methods of the Research: The type of research used in this paper is normative legal research. As for answering the problems in this study, the authors use three approaches to the problem, namely the statutory approach (statute approach), conceptual approach (conceptual approach) and case approach (case approach). The procedure for collecting legal materials carried out by the author is by searching for and collecting laws and regulations related to the legal issues at hand. Legislation in this case includes both legislation and regulation. Analysis of legal material uses qualitative methods, namely studies related to legal norms contained in international law legislation and legal norms that exist in society.Results of the Research: The results of this study indicate that the arrangements for the rights of indigenous peoples over natural resources based on the ICESCR contained in Articles 6 to 25 recognize the basic rights of everyone in the economic, social and cultural fields. Included are indigenous peoples who are legal subjects so they have rights and obligations. The rights of indigenous peoples over natural resources have not been implemented in accordance with the ICESCR legal instruments, even though Indonesia itself has ratified these legal instruments with Law no. 11 of 2005 so that there is a responsibility or obligation for the State to submit and comply with this instrument.